HISTOLOGICAL INDICATORS OF GRAY LAMBS OF DIFFERENT COLORS OF JACKET-SMUSH TYPE (Experimental biology, 2023)
Currently, in a market economy, there are a number of problems that impede the improvement of the quality of karakul. One of them is the need to improve effective methods of selection and breeding, taking into account the characteristics of karakul sheep, in-depth study of the histomorphological structures of the skin and wool of lambs of different colors and increase the productivity of karakul sheep.The purpose of this study is to study the histomorphological features of lambs of different colors of the jacket-type lambs obtained from gray karakul sheep.According to the results of the study, in dark gray lambs of the mother-of-pearl jacket type, the thickness of the reticular layer of the skin was 532.2; in dark gray lambs - 537.7 microns, or by 43.4% (8.78%) and 46.5 (9.47%) are fatter than light gray milky and medium gray jacket blue lambs (P < 0.05).It can be seen that the diameter of the secondary hair follicles in lead-colored medium-gray lambs is 1.48% and 7.44% thicker than in steel-colored and blue-colored dark gray lambs, respectively. The coefficient of deviation of the diameter of hair secondary hair follicles ranged from Cv = 15.6-20.5.According to the number of secondary hair follicles, it can be seen that in lambs of light gray color of steel of the jacket type, it is 6.04% and 9.79% more than in lambs of light gray color of blue and mother-of-pearl colors (P
Keywords: karakul, coloration, epidermis, pylar layer, reticular layer.